O domínio ocidental na esfera epistemológica do direito angolano: a visão dos estudantes das universidades públicas sobre a continuidade colonial - Inácio da Ressurreição Mamboma Luemba (2022)
The theme "The Western domain in the epistemological sphere of Angolan Law" is a study that proposes, through the vision of Law students from Angolan Public Universities, to reflect on the relations of Western domain in the epistemic field of Law teaching and its impacts in the cultural dimension of the Angolan peoples. We seek to understand the visions, points of view and perspectives of these students about Law, aiming to diagnose the tensions generated by the colonizing impositions present in the curricula of seven Law courses in Angola. For this purpose, we applied a survey questionnaire and held focus group sessions. Around this methodological itinerary, we highlight the documentary research, which aimed to proceed with the collection, for the purposes of analysis, of several documents that constitute Angolan Law and its teaching in Angolan Public Universities. The study appropriates the theoretical contributions of decolonial studies of the Modernity/Coloniality group (CASTRO-GÓMEZ and GROSFOGUEL, 2007), as well as Critical Discourse Analysis (CDA). The analyzes point to the presence of colonized/colonizing discourses in these documents; and resistance/submission discourses in the students' statements and testimonies. Our final considerations highlight three scenarios, namely, how Angolan Law and its teaching in Angolan Public Universities is dominated by the West; the omission of cultural aspects of the peoples of Angola in the teaching of Law in Angola; and the legal tensions, conflicts and contradictions faced by the Angolan legal community.